Monocyte to HDL Cholesterol Ratio (MHR) and Monocyte to Lymphocyte Ratio (MLR) in Overweight and Obese Women - Novitasari SOESILO; Meita HENDRIANINGTYAS; Devi Elvina RACHMA; Edward Kurnia Setiawan LIMIJADI (Modern Medicine)
Background: The prevalence of obesity and overweight in Indonesian women will continue to increase. Obesity and overweight conditions are often associated with low-grade inflammatory conditions and metabolic syndrome. The ratio of monocytes to HDL cholesterol (RMH) and the ratio of monocytes to lymphocytes (RML) are easy tests to monitor inflammation associated with increased body mass index and cardiovascular disorders due to metabolic syndrome. Objective: To analyze the differences in RMH and RML in obese and overweight women. Methods: The cross-sectional study was conducted in the outpatient laboratory at the Diponegoro National Hospital (RSND). This study included 55 overweight women (BMI 25.00 – 29.99 kg/m2) and 55 obese women (BMI ≥ 30 kg/m2), healthy, aged 25-45 years. Research subjects were excluded with the criteria of not having hypertension, liver disorders, and diabetes mellitus. RMH is obtained by dividing the absolute monocyte count by HDL cholesterol. RML is obtained by dividing the absolute monocyte and lymphocyte counts. Monocyte and lymphocyte numbers were obtained by examining a Complete Blood Count (CBC) using an automatic hematology analyzer. HDL cholesterol levels were measured by enzymatic methods using a clinical chemistry analyzer. Statistical analysis with the Mann-Whitney test. Results: There is a difference in RMH between obese and overweight women (p = 0.003). There was no difference in RML (p = 0.342) between the two groups. Conclusion: Obese women have a significantly higher RMH than overweight. RMH can be used as an assessment of inflammatory conditions and is used as a clinical alert for various health problems in obese and overweight women.